Development and reliability and validity testing of a medication literacy scale for medical college students - Zeng Leixiao; Sun Xiaonan; Pan Lutong; Gu Wenjing; Xiao Chang; Tang Jingqi; Dai Wenting; Kang Xiuqin; Wu Yibo (BMC Medical Education)
Abstract Background Irrational drug use has become a global problem threatening human health. As future health professionals, medical college students’ medication literacy (ML) is critical. Their mastery of medication-related knowledge will directly affect public medication safety in the future. Methods The initial scale was developed through a literature review and was modified through expert consultation and student interviews to form the initial scale with 14 items. In 2020, a questionnaire survey was conducted among students in a medical college for item analysis, reliability test, validity test and other analyses. Results The total Cronbach’s α coefficient was 0.826 and split-half reliability was 0.852. The Cronbach’s α coefficients for functional medication literacy, communicative medication literacy, and critical medication literacy were 0.901, 0.858, and 0.851, respectively. The item-level content validity index (I-CVI) ranged from 0.833 to 1.000 (≥ 0.78). Factor analysis of 14 items showed that KMO = 0. 852(> 0.7) and Bartlett’s spherical test p < 0.001, indicating that the data are very suitable for factor analysis. Three principal axis factors were extracted by principal component analysis, and the total variance interpretation rate was 69.031% (> 40%). The confirmatory factor analysis identified a three-factor model and showed goodness of fit indices for the scale: The χ²/df = 2.623, The Goodness of Fit Index (GFI) = 0.905, The Comparative Fit Index (CFI) = 0.950, Normed Fit Index (NFI) = 0.922, Tucker-Lewis index (TLI) = 0.938, and The Root Mean Square Error of Approximation (RMSEA) = 0.078. Conclusion A new scale for evaluating the medication literacy of Chinese medical college students was preliminarily developed, demonstrating good reliability and validity. Itcan be used as a preliminary measurement tool for assessing medical students’ medication literacy. However, due to the limitations of this study, the practical application of the scale needs to be further examined in a larger sample and should be refined in future studies.